Prazosin Can Prevent Glucocorticoid Mediated Capillary Rarefaction - Mandel, Erin R. (PLoS One, 2016)
Glucocorticoids (GC) elicit skeletal muscle capillary rarefaction, which can subsequently impair blood distribution and muscle function; however, the mechanisms have not been established. We hypothesized that CORT would inhibit endothelial cell survival signals but that treatment with the alpha-1 adrenergic receptor inhibitor prazosin, which leads to angiogenesis in skeletal muscle of healthy rats, would reverse these effects and induce angiogenesis within the skeletal muscle of corticosterone (CORT)-treated rats. Male Sprague Dawley rats were implanted subcutaneously with CORT pellets (400 mg/rat), with or without concurrent prazosin treatment (50mg/L in drinking water), for 1 or 2 weeks. Skeletal muscle capillary rarefaction, as indicated by a significant reduction in capillary-to-fiber ratio (C:F), occurred after 2 weeks of CORT treatment. Concurrent prazosin administration prevented this capillary rarefaction in CORT-treated animals but did not induce angiogenesis or arteriogenesis as was observed with prazosin treatment in control rats. CORT treatment reduced the mRNA level of Angiopoietin-1 (Ang-1), which was partially offset in the muscles of rats that received 2 weeks of co-treatment with prazosin. In 2W CORT animals, prazosin treatment elicited a significant increase in vascular endothelial growth factor-A (VEGF-A) mRNA and protein. Conversely prazosin did not rescue CORT-induced reductions in transforming growth factor beta-1 (TGFβ1 and matrix metalloproteinase-2 (MMP-2) mRNA. To determine if CORT impaired shear stress dependent signaling, cultured rat skeletal muscle endothelial cells were pre-treated with CORT (600nM) for 48 hours, then exposed to 15 dynes/cm(2) shear stress or maintained with no flow. CORT blunted the shear stress-induced increase in pSer473 Akt, while pThr308 Akt, ERK1/2 and p38 phosphorylation and nitric oxide (NO) production were unaffected. This study demonstrates that GC-mediated capillary rarefaction is associated with a reduction in Ang-1 mRNA within the skeletal muscle microenvironment and that concurrent prazosin treatment effectively increases VEGF-A levels and prevents capillary loss.